Identifying ventilatory anaerobic threshold in children and adolescents: A literature review. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n3p343 - Luciana Carletti; Anselmo José Perez (Universidade Federal de Santa Catarina, 2012)
Ventilatory anaerobic threshold (VAT) has been used in research to represent pulmonary function and submaximal performance capacity of children and adolescents. This study aimed to identify: a) the group of children and adolescents that has been the main focus of research; b) the criteria most commonly used to determine VAT; and c) the main references that have been used to support the theoretical analysis. A literature search was conducted using LILACS, MEDLINE/PubMed, and SciELO. The search was limited to studies using VAT in their methodology, published between 2000 and 2010, in order to identify categories through content analysis. Descriptive statistics were used to analyze the data. Forty-five studies were found and distributed according to categories identified, as follows: severe exercise intolerance (23 [51%]); healthy subjects (6 [13%]); obese subjects and comparison of methodologies (4 [9%], each); O2 kinetics (3 [7%]); sports (2 [4%]); stunting, asthma, and effort perception (1 [2%], each). The main reference used is Beaver WL, Wasserman K, Whipp BJ (1986), cited in 24 (53%) studies, and the main criterion for VAT determination is the V-slope method. In addition to this method, ventilatory equivalents for O2 and CO2 have been used, accounting for 37% (17) of cases. In conclusion, the dataindicate that VAT has been primarily used in rehabilitation studies including children and adolescents by the V-slope method.